PENGARUH TEKNOLOGI INFORMASI TERHADAP KEWAJIBAN KERAHASIAAN DAN PERLINDUNGAN DATA PRIBADI KLIEN DALAM PRAKTIK NOTARIS - Sophia Afifa Nasution; Siti Hajati Husein (Media Bina Ilmiah, 2025)
This study explores the impact of information technology on the obligations of confidentiality and the protection of clients' personal data in notarial practice in Indonesia, amidst the rapid development of digital technology that increases the risk of privacy violations. A qualitative research method, combining literature review and interviews, was used to identify the legal basis and practical challenges faced by notaries in safeguarding personal data, in accordance with the Personal Data Protection Act (UU PDP) and the Notary Position Act (UU JN). The findings reveal that while the PDP Act provides an essential legal framework, the implementation of information technology adds complexity to personal data management, requiring strict security measures such as encryption and password management. Consistent application of data protection principles and rigorous oversight are critical to preventing violations, with strict sanctions serving as a driver for compliance. The involvement of all stakeholders—government, private sector, and society—is key to creating a secure and ethical environment for personal data management, thereby supporting the sustainable development of technology.